2022
DOI: 10.3389/fonc.2021.781833
|View full text |Cite
|
Sign up to set email alerts
|

Standardizing Patient-Derived Organoid Generation Workflow to Avoid Microbial Contamination From Colorectal Cancer Tissues

Abstract: The use of patient-derived organoids (PDO) as a valuable alternative to in vivo models significantly increased over the last years in cancer research. The ability of PDOs to genetically resemble tumor heterogeneity makes them a powerful tool for personalized drug screening. Despite the extensive optimization of protocols for the generation of PDOs from colorectal tissue, there is still a lack of standardization of tissue handling prior to processing, leading to microbial contamination of the organoid culture. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Marinucci et al. ( 151 ) attempted to standardize washing protocols and antibiotic use to prevent contamination. They found that non-washed samples had a contamination rate of 62.5%, which decreased to 50% and 25% with PBS or p/s-containing PBS, respectively.…”
Section: Standardizing the Prevention Of Microbial Contamination In O...mentioning
confidence: 99%
See 3 more Smart Citations
“…Marinucci et al. ( 151 ) attempted to standardize washing protocols and antibiotic use to prevent contamination. They found that non-washed samples had a contamination rate of 62.5%, which decreased to 50% and 25% with PBS or p/s-containing PBS, respectively.…”
Section: Standardizing the Prevention Of Microbial Contamination In O...mentioning
confidence: 99%
“…They found that non-washed samples had a contamination rate of 62.5%, which decreased to 50% and 25% with PBS or p/s-containing PBS, respectively. Interestingly, none of the organoid cultures washed with PBS/primocin were contaminated ( 151 ). Moreover, adding p/s to the washing solution reduced cell viability compared to primocin ( 151 ).…”
Section: Standardizing the Prevention Of Microbial Contamination In O...mentioning
confidence: 99%
See 2 more Smart Citations
“…The success rate of culture may be further improved by obtaining multiple biopsies and direct evaluation by pathologists ( 119 ). CRC organoids with different histological subtypes have been described to be successfully constructed and clinical parameters, such as tumor size or presence of ulcers, were not associated with the occurrence of contamination ( 55 , 80 , 120 ). However, the establishment of organoids from tumors with rare CRC histologic subtypes (e.g., poorly differentiated adenocarcinoma, mucinous adenocarcinoma and neuroendocrine carcinoma) is more difficult ( 33 ).…”
Section: Limitations Of Crc Organoids and Solutionsmentioning
confidence: 99%